Factors influencing the performance of a banking solution for the unbanked in South Africa - Ramugondo, Emmanuel Tumelo (My University, 2016)
Two decades since South Africa became a democratic state, a significant number of South Africans still have limited or no access to banking services, with poor communities continuing to suffer financially in order to access banking services (Competition Commission South Africa, 2008). FinMarkTrust (2014) estimates that of the 36.8 million South Africans above 16 years of age who are eligible to open a bank account, approximately 9.3 million of them do not hold any banking product. Of the 9.3 million people who do not have a bank product, just over 7.3 million of them have never opened a bank account. Both government and financial institutions have implemented several initiatives aimed at increasing financial inclusion and improve access to banking. The objective of this report is therefore to determine factors influencing the performance of banking solutions aimed at banking the unbanked in South Africa. A case study of FNB’s banking solutions for the unbanked was done to determine factors that influence performance of FNB’s banking solutions for the unbanked. A questionnaire was sent to 8 middle and senior managers responsible for the design, distribution, marketing and sales of FNB’s banking solutions aimed at banking the unbanked. It was determined that price, location of banking channels or services and below the line marketing have an impact on the ability of a banking solution to attract or retain poor consumers. It was also determined that banks have to focus on addressing specific challenges that prevent the unbanked to be banked when designing banking solutions for the unbanked, this is a key factor that enables acceptability of the banking products by the poor. Thus, if the banking solution meets the needs of the poor, it will be accepted and used by the poor, thereby help reduce people with no access to banking services.
MBA
Keywords: Banks and banking -- Customer services -- South Africa. Financial services industry -- South Africa.Low-income consumers -- South Africa.